Developing Algorithm for Matching Arabic Names Entered by Mobile Phone - Alsorori, Muneer; Sanabani, Maher Al-; Hagree, Salah AL-; Abdulmalik, Sarah; AlArhabi, Noor Al-Huda; Abdu, Suad; Meqran, Khawlah (International Journal For Research In Advanced Computer Science And Engineering, 2019)
Name matching plays a vital and crucial role in many applications. They are for example used in information retrieval or deduplication systems to do comparisons among names to match them together or to find the names that refer to identical objects, persons, or companies. Since names in each application are subject to variations and errors that are unavoidable in any system and because of the importance of name matching, so far many algorithms have been developed to handle matching of names. These algorithms consider the name variations that may happen because of spelling, pattern or phonetic modifications. However most existing methods were developed for use with the English language and so cover the characteristics of this language. Up to now no specific one has been designed and implemented for the Arabic language. The purpose of this study is to present a name matching algorithm for Arabic language. In this project, after consideration of all major algorithms in this area, we selected one of the basic methods for name matching that we then expanded to make it work particularly well for Arabic names. This proposed new algorithms based on the convergence and spacing between the Arabic characters in the keyboard of the mobile phone in order to give more accurate results for Arabic names. In this study the experiments have been accomplished in order to evaluate the proposed algorithm (LD_F,LD_S and LD_KE). The first experiment has been carried for the proposed algorithms (LD_F,LD_S,LD_KM and LD_KE). This experiment is carried based on F-Dataset which has 15 pairs of names. The result of the experiment showed that the proposed algorithms gave more accurate results than the Levenshtein algorithm. Therefore, it can be used in many applications such as Automatic Spell Correction (ASC), Search Engines (SE), Data Retrieval (DR), Computational Biology “DNA” ,Customer Relation Management (CRM), Customer Data Integration (CDI), AntiMoney Laundering (AML) and Criminal Investigation (CI).